A novel magnetic-driven tissue retraction device for minimally invasive surgery. Issue 1 (2nd January 2017) - Brancadoro, Margherita; Tognarelli, Selene; Ciuti, Gastone; Menciassi, Arianna
Abstract: Introduction: The purpose of this work is to design and validate an innovative magnetic-based device for tissue retraction for minimally invasive surgery. Material and methods: An intra-abdominal magnetic module is coupled with an extracorporeal system for establishing a stable attraction, and consequently a reliable tissue retraction. Once the retractor has been inserted into the abdomen, tissue retraction is not constrained by a fixed access port, thus guaranteeing a more flexible, safer and less invasive operation. The intra-abdominal unit is composed of an axial permanent magnet attached to a stainless-steel non-magnetic alligator clip by a traditional suturing thread. A miniaturized mechanism to adjust the length of the suturing thread for lengthening or shortening the distance between the tissue grasper and the internal magnetic unit is included. A multiphysics approach assured a dedicated design that thoroughly fulfills anatomical, physiological and engineering constraints. Results: System functionalities were demonstrated both in in-vitro and ex-vivo conditions, reaching good results and promising outcomes in terms of effectiveness and maneuverability. The retractor was successfully tested in an animal model, carrying out a whole retraction procedure. Conclusion: The proposed retraction system resulted to be intuitive, reliable, robust and easy to use, representing a suitable device for MIS procedures.